FACTORS HINDERING MEN FROM SUPPORTING THEIR SPOUSES IN LABOR AND DELIVERY AT SSEKAMULI HEALTH CENTER III, LUWEERO DISTRICT. A CROSS-SECTIONAL STUDY. - Adima , Gerald; NABUKENYA, SHARIFAH (Student's Journal of Health Research Africa, 2023)
Background: The study aimed to identify individual, socio-economic, and health-related factors hindering men from supporting their spouses during labor and delivery at Sekamuli Health Centre III in Luweero district. Methodology: A descriptive cross-sectional study design with a Simple random sampling technique was used. Data was collected on the sample size of 50 respondents using a semi-structured questionnaire written in the English language with open and closed-ended questions as a data collection tool. Results: 60% had ever discussed with their partner issues related to their involvement in labor, (53.3%) were encouraged by their wives, (70%) had ever been treated differently by women where (77.1%) were not welcomed women in maternity, (66%) were unemployed and (72%) were not allowed in their culture to see their wives during labor. (70%) were taught once about male involvement in labor, 56% had never escorted their wives to a health facility during labor, (57.1%) waited for their wives during labor and delivery for 24 hours, (66%) resided a distance between 5km-9km from the healthy facility, (68%) health workers had good attitudes towards male involvement in labor and 80% men had no space for accommodation during labor and delivery at the facility. Conclusion: Inadequate knowledge (64%), poor perception (74%), unemployment (66%), low educational level (54%), cultural belief (72%), long waiting time (77%), long distance (66%) and inadequate space (80%) were the factors hindering men from supporting their spouses during labor and delivery. Recommendation: The administrators and health workers of Sekamuli Health Centre; should continue sensitizing and educating the importance of male involvement in maternal and childbirth to eliminate cultural norms and beliefs like men are not allowed in labor and men thinking that labor and delivery are women's duty such as that men can fulfill their responsibility during labor and delivery.